1999
DOI: 10.1890/1051-0761(1999)009[1179:ootuon]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Use of Natural Variability Concepts in Managing Ecological Systems

Abstract: Natural resource managers have used natural variability concepts since the early 1960s and are increasingly relying on these concepts to maintain biological diversity, to restore ecosystems that have been severely altered, and as benchmarks for assessing anthropogenic change. Management use of natural variability relies on two concepts: that past conditions and processes provide context and guidance for managing ecological systems today, and that disturbance-driven spatial and temporal variability is a vital a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
507
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 543 publications
(527 citation statements)
references
References 44 publications
(41 reference statements)
7
507
0
1
Order By: Relevance
“…Studies that track the long-term response of native community diversity, abundance, evenness, population demography, and relative dominance to invasive species are rare, and valuable (Strayer et al 2006). The principal advantage of long-term studies is that they do not require making assumptions about the past condition of a site, unlike studies that substitute space for time (Johnson and Miyanishi 2008;Landres et al 1999). However, the frequency of monitoring confounding site conditions such as disturbance, determines the quality of data collected through long-term observations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that track the long-term response of native community diversity, abundance, evenness, population demography, and relative dominance to invasive species are rare, and valuable (Strayer et al 2006). The principal advantage of long-term studies is that they do not require making assumptions about the past condition of a site, unlike studies that substitute space for time (Johnson and Miyanishi 2008;Landres et al 1999). However, the frequency of monitoring confounding site conditions such as disturbance, determines the quality of data collected through long-term observations.…”
Section: Introductionmentioning
confidence: 99%
“…The role that paleoecology could play in addressing these issues was recognized as scientists and resource managers debated (1) what constitutes an appropriate baseline or reference condition for restoration given the extent of anthropogenic alterations to natural systems; (2) how to account for processes that occur infrequently or very slowly over decadal to centennial timescales and (3) what are the appropriate spatial and temporal scales for understanding ecosystems (Davis, 1989;Swetnam and Betancourt, 1998;Landres et al, 1999;Swetnam et al, 1999;Jackson and Overpeck, 2000;Jackson, 2001;Flessa, 2002). The U.S. National Academy of Sciences Committee on Restoration of Aquatic Ecosystems published a report in 1992 (NRC, 1992) that discussed the need for baseline studies and identified paleoecology as a method for obtaining information on the historic condition of ecosystems.…”
Section: Application To Restoration and Resource Managementmentioning
confidence: 99%
“…The U.S. National Academy of Sciences Committee on Restoration of Aquatic Ecosystems published a report in 1992 (NRC, 1992) that discussed the need for baseline studies and identified paleoecology as a method for obtaining information on the historic condition of ecosystems. By the end of the 1990s, the value of historical information on ecosystem variability and the use of paleoecology to obtain this information were increasingly recognized as essential components in resource management decisions (Landres et al, 1999;Millar and Woolfenden, 1999;Parsons et al, 1999;Swetnam et al, 1999).…”
Section: Application To Restoration and Resource Managementmentioning
confidence: 99%
“…It is also recognised that the failure to maintain the diversity of natural processes has been a major cause of ecosystem degradation (Landres et al, 1999;Francis, 2009). For instance, attempts to control the natural variability of fluvial ecosystems inevitably lead to ecosystem degradation, and often pose a substantial risk to humans (for example the many problems associated with the management and prediction of flood risks; Apel et al, 2004).…”
Section: Ecosystem Variability and Maintenance Of River Island Landscmentioning
confidence: 99%